Let's Ask the Other Side: Teaching Gymnasium Plant Biology from a Teacher's Perspective - Jozef Kováčik; Marek Vydra (MDPI AG, 2023)
It has been repeatedly found that plant biology is less attractive for students than other biology fields. We, therefore, focused on the opposite and, through an online questionnaire, we asked biology teachers at gymnasia throughout Slovakia how they teach plant biology and where they experience problems. Almost 30% of teachers characterized technical equipment as insufficient but use some visual aids for ca. 50% of lessons. Despite the dominant use of microscopy, teachers admit that students' biggest shortcomings are found in the anatomy of organs, photosynthesis, ontogenesis and its regulation by exogenous/endogenous factors, or when connecting knowledge about tissues with their functions. About half of the teachers rate their knowledge of plant anatomy and physiology as sufficient, but these teachers rate only about 20% of their students in the same way. Based on the negative correlation between the use of aids and the lack of student knowledge, and, at the same time, the positive correlation between the activity of teachers and better technical equipment, we conclude that the mainly neglected technical infrastructure does not allow for a better practical education (e.g., only 13.7% of gymnasia have analytical balances and only 1.6% a spectrophotometer). Furthermore, almost 90% of teachers mentioned that online education during COVID-19 pandemic negatively affected students' knowledge. We hope that our research can contribute to changes in the Slovak educational curriculum focused on plant biology in a more scientific direction and inspire research in other countries, with the aim of exchanging knowledge regarding the species diversity of plants around the world and their importance for people and the environment.